THE MODEL OF LAW ON THE FULFILLMENT OF RIGHT TO EDUCATION AS THE CONSTITUTIONAL RIGHT OF CITIZENSHIP IN TERRITORIAL BORDER - Aditia Syaprillah; Yahya Ahmad Zein (Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractVarious weaknesses are still found in the protection of the rights of citizens, pertaining to the right to education in border area, that resulted in the backwardness and poverty of its citizens. The government of Nunukan District has released a regulation in fulfilling the right to education of citizens, that is regional regulation Number 05 Year 2012 on the management and implementation of education. Legal model for the fulfillment of the right to education of citizens in the border area should refer to the constitutional rights of citizens and in accordance with the international covenant on ECOSOC rights and principles of national education. IntisariPersoalan kebijakan perlindungan hak-hak warga negara khususnya terkait hak pendidikan di wilayah perbatasan selama ini masih terdapat berbagai macam kelemahan yang berakibat keterbelakangan, ketertinggalan dan kemiskinan warga negara di wilayah perbatasan. Kebijakan Pemda Kab. Nunukan dalam rangka pemenuhan hak atas pendidikan warga negara di wilayah perbatasan dituangkan ke dalam Perda Nomor 05 tahun 2012 tentang Pengelolaan Dan Penyelenggaraan Pendidikan. Model hukum Pemenuhan hak atas pendidikan warga negara di wilayah perbatasan harus mengacu pada hak konstitusional Warga Negara yang dijamin dalam konstitusi Indonesia dan sesuai dengan Konvenan Internasional Hak Ekosob dan prinsip-prinsip penyelenggaraan pendidikan nasional.